Malnourished Under-Five Children Feeding Practices in Cipacing Village 2012 - Fujianti, Shinta Tresna; Herawati, Dewi Marhaeni Diah; Kadi, Fiva Aprilia (Althea Medical Journal, 2015)
Â Â Â Background: Maternal parenting, especially feeding practices, is very important in childhood period and may affect the childâs nutritional state. Proper nutrition affects the growth and development of children. The aim of this study is to describe parenting feeding practices in malnourished under-five children.Methods: A descriptive study on 43 mothers with malnourished under-five children aged 12â59 months was performed in Cipacing Village, Jatinangor, Sumedang during the periode of OctoberâNovember 2012.Â Results: The composition of children based on their malnutrition status and description on good and poor parenting were presented in the result. Twenty two children (51.2%) were severely under nourished, 18 children (41.9%) were under nourished, and 3 children (7%) experienced overweight. Good maternal parenting was identified in child nurturing (86%), feeding frequency (93%), feeding style (62.8%), and situation of feeding (74.4%) while poor maternal parenting was observed in feeding time (55.8%) and types of food given (51.2%).Â Conclusions: Maternal parenting plays an important role in children nutrition status.Keywords: Children, feeding practice, malnutrition, maternal parentingDOI: 10.15850/amj.v2n1.435Â